Data Acquisition of PV Mini-Grid Voltage and Current using Arduino and PLX-DAQ - Anggi Murfianah; Krismadinata Krismadinata; Yoan Elviralita (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2021)
Solar panels are the main equipment for a solar power generation system that functions to convert sunlight energy directly into electrical energy. The solar panel performance monitoring system is designed to be equipped with current and voltage measuring sensors that have been integrated into an Excel Spreadsheet using the PLX-DAQ application program. Arduino Nano based system design and connected to a computer via USB. The advantage of this monitoring system is that measurement results from sensors can be processed directly and displayed in the form of data and graphics in real time conditions. This makes it easy for data processing. Panel surya adalah peralatan utama sistem pembangkit listrik tenaga surya yang berfungsi untuk mengkonversikan energi cahaya matahari menjadi energi listrik secara langsung. Untuk memenuhi keperluan pemantauan output panel surya, sistem pemantauan (monitoring) kinerja panel surya dirancang dilengkapi dengan sensor pengukur arus dan tegangan yang diintegrasikan ke Spreadsheet Excel menggunakan program aplikasi PLX-DAQ. Perancangan sistem berbasis Arduino nano dan dihubungkan ke komputer melalui USB. Kelebihan dari sistem pemantauan ini adalah hasil pengukuran dari sensor dapat diproses secara langsung dan ditampilkan dalam bentuk data dan grafik pada kondisi real time. Hal ini memberikan kemudahan untuk pengolahan data.